Activating mTOR mutations in a patient with an extraordinary response on a phase I trial of everolimus and pazopanib - Wagle, Nikhil (2014)
Understanding the genetic mechanisms of sensitivity to targeted anticancer therapies may improve patient selection, response to therapy, and rational treatment designs. One approach to increase this understanding involves detailed studies of exceptional responders: rare patients with unexpected exquisite sensitivity or durable responses to therapy. We identified an exceptional responder in a phase I study of pazopanib and everolimus in advanced solid tumors. Whole exome sequencing of a patient with a 14-month complete response on this trial revealed two simultaneous mutations in mTOR, the target of everolimus. In vitro experiments demonstrate that both mutations are activating, suggesting a biological mechanism for exquisite sensitivity to everolimus in this patient. The use of precision (or “personalized”) medicine approaches to screen cancer patients for alterations in the mTOR pathway may help to identify subsets of patients who may benefit from targeted therapies directed against mTOR.